PERANAN TV ONE MELALUI PROGRAM ACARA INDONESIA LAWYERS CLUB DALAM MANAJEMEN KONFLIK - Tita Melia Milyane (Prodi Ilmu Komunikasi FISIP Universitas Langlangbuana, 2016)
This paper examines one of the television program on TV One who has a talk show program Indonesia Lawyers Club , where through this program the public are invited to jointly examine, explore and think about various legal issues that are going on in Indonesia. With the hosts Karni Ilyas, the event was able to hit a lot of the audience, it is evident that this event is a program of events with the highest rating based on a survey conducted three Indonesian Broadcasting Commission (KPI) with the Association of Indonesian Communication (ISKI) in 2015. The results of the review of research finds that this event is one of the events that manage the ongoing conflict, with the sources-related resource persons who have the opposite view. This program also shows that the conflict can be has or managed by third parties, to get the thread of the issues being discussed. The event also had an impact in educating the public, especially in terms of law enforcement, legislation and political issues in Indonesia.